2023
DOI: 10.1002/ppul.26567
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography in hospitalized children: Characteristics and clinical practice at a single tertiary care center

Abstract: BackgroundPolysomnography (PSG) is the gold standard for the diagnosis of pediatric sleep‐disordered breathing (SDB). However, the literature characterizing the indications for inpatient PSGs and the impact on clinical decision‐making is limited.ObjectiveTo determine the indications, results, and outcomes for children undergoing inpatient PSGs at our institution.MethodsWe performed a retrospective review of children aged 0–18 years who underwent inpatient diagnostic PSGs between July 2018 and July 2021 at Sick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…INS have an anti-inflammatory effect that reduces the release of inflammatory mediators and inhibits inflammatory cell recruitment to the nasal mucosa [43]. It was demonstrated that inflammatory mediators and their expression is increased in the nose and pharynx of patients with OSA [44]. In support of this, neutrophilic cells in sputum and elevated inflammatory markers (leukotrienes, prostaglandins) in exhaled breath condensate were found.…”
Section: Intranasal Steroids (Ins)mentioning
confidence: 86%
See 2 more Smart Citations
“…INS have an anti-inflammatory effect that reduces the release of inflammatory mediators and inhibits inflammatory cell recruitment to the nasal mucosa [43]. It was demonstrated that inflammatory mediators and their expression is increased in the nose and pharynx of patients with OSA [44]. In support of this, neutrophilic cells in sputum and elevated inflammatory markers (leukotrienes, prostaglandins) in exhaled breath condensate were found.…”
Section: Intranasal Steroids (Ins)mentioning
confidence: 86%
“…Furthermore, the presence of two isoforms of glucocorticoid receptors (GRC-alpha and GCR-beta) were demonstrated in adenoid and tonsil tissues [45]. It is not known whether this receptor expression is a cause or a consequence of the disease, but it is associated with a greater response to INS therapy in children with OSA [44]. Lastly, lowgrade chronic systemic inflammation was also described, as demonstrated by the increase in the serum C-reactive protein and proinflammatory cytokines [10,46].…”
Section: Intranasal Steroids (Ins)mentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-inflammatory therapies, such as topical steroids, can be useful [66] by reducing the release of inflammatory mediators that may cause nasal obstruction in individuals with allergic rhinitis and adenoid hypertrophy [67,68]. The use of inhaled steroids, compared to systemic steroids, results in lower systemic absorption by acting locally on the nasal mucosa [69]. The most commonly used corticosteroids are budesonide, fluticasone, and mometasone [67].…”
Section: Pharmacological Therapymentioning
confidence: 99%